Effect of pulmonary rehabilitation on heart rate recovery in adult individuals with asthma or chronic obstructive pulmonary disease - Zampogna, Elisabetta; Ambrosino, Nicolino; Oliva, Federico Mattia; Rudi, Monica; Sotgiu, Giovanni; Saderi, Laura; Spanevello, Antonio; Visca, Dina (Frontiers in Pharmacology, 2022)
Introduction: Heart rate recovery (HRR) after exercise is a marker of disease severity and prognosis in cardiovascular and respiratory disorders. More than 30% of adult individuals with asthma may show a slow HRR. Pulmonary rehabilitation improves exercise capacity in individuals with asthma or chronic obstructive pulmonary disease (COPD). Aim: The study aimed to evaluate the effect of pulmonary rehabilitation on HRR in individuals with asthma as compared to those with COPD. Methods: Retrospective analysis of HRR one minute after the six-minute walking test (6MWT) was performed before and after an exercise training program. The COPD Assessment Test (CAT), Barthel Index-Dyspnea (BI-D), Medical Research Council (MRC) score for dyspnea, and the Five-Times-Sit-to-Stand test (5STS) were also assessed as secondary outcome measures. Results: Slow HRR prevalence was significantly lower in individuals with asthma than with COPD (29.1 vs. 46.7%, respectively: p = 0.003). Post-program HRR did not change in more than 70% of individuals in either population and improved in 16% of both populations, whereas it actually worsened in 12 and 10% of individuals with asthma and COPD, respectively. The outcome measures significantly improved in both populations, irrespective of baseline HRR. Conclusion: In individuals with asthma or COPD, exercise training does not significantly improve HRR.